Rhinovirus C Infection Induces Type 2 Innate Lymphoid Cell Expansion and Eosinophilic Airway Inflammation - Rajput, Charu; Han, Mingyuan; Ishikawa, Tomoko; Lei, Jing; Goldsmith, Adam M.; Jazaeri, Seyedehzarifeh; Stroupe, Claudia C.; Bentley, J. Kelley; Hershenson, Marc B. (Frontiers in Immunology, 2021)
Rhinovirus C (RV-C) infection is associated with severe asthma exacerbations. Since type 2 inflammation is an important disease mechanism in asthma, we hypothesized that RV-C infection, in contrast to RV-A, preferentially stimulates type 2 inflammation, leading to exacerbated eosinophilic inflammation. To test this, we developed a mouse model of RV-C15 airways disease. RV-C15 was generated from the full-length cDNA clone and grown in HeLa-E8 cells expressing human CDHR3. BALB/c mice were inoculated intranasally with 5 x 106 ePFU RV-C15, RV-A1B or sham. Mice inoculated with RV-C15 showed lung viral titers of 1 x 105 TCID50 units 24 h after infection, with levels declining thereafter. IFN-α, β, γ and λ2 mRNAs peaked 24-72 hrs post-infection. Immunofluorescence verified colocalization of RV-C15, CDHR3 and acetyl-α-tubulin in mouse ciliated airway epithelial cells. Compared to RV-A1B, mice infected with RV-C15 demonstrated higher bronchoalveolar eosinophils, mRNA expression of IL-5, IL-13, IL-25, Muc5ac and Gob5/Clca, protein production of IL-5, IL-13, IL-25, IL-33 and TSLP, and expansion of type 2 innate lymphoid cells. Analogous results were found in mice treated with house dust mite before infection, including increased airway responsiveness. In contrast to Rorafl/fl littermates, RV-C-infected Rorafl/fl Il7rcre mice deficient in ILC2s failed to show eosinophilic inflammation or mRNA expression of IL-13, Muc5ac and Muc5b. We conclude that, compared to RV-A1B, RV-C15 infection induces ILC2-dependent type 2 airway inflammation, providing insight into the mechanism of RV-C-induced asthma exacerbations.